Net Heterotrophy in the Amazon Continental Shelf Changes Rapidly to a Sink of CO2 in the Outer Amazon Plume - Lefèvre, Nathalie; Flores Montes, Manuel; Gaspar, Felipe L.; Rocha, Carlos; Jiang, Shan; De Araújo, Moacyr C.; Ibánhez, J. Severino Pino (Frontiers in Marine Science, 2017)
The Amazon continental shelf and adjacent oceanic area were sampled for inorganic and organic carbon parameters in order to improve data coverage and understanding of carbon cycling dynamics within this important region. Seasonal coverage of the Amazon plume on the French Guiana continental shelf further north, was provided by CO2 monitoring using a merchant ship sailing from France to French Guiana (2006-2016). Salinity ranged from 1 to 36 (transects in April 2013, and May 2014). At salinity below 10, strong outgassing was observed with fugacity of CO2 (fCO2) over 2000 atm. This region displayed net heterotrophy, fueled by organic matter with terrestrial origin, as shown by 13C and 15N values of suspended particles. A 13C cross shelf average of -31‰ was measured during May 2014, contrasting with oceanic values in excess of -20‰. The reactivity of this terrestrial material resulted in the local production of dissolved inorganic and organic carbon as well as fluorescent humic compounds. Further offshore, the dilution of freshwater by ocean waters created a sink for CO2, enhanced by biological activity. The strongest CO2 drawdowns, associated with high chlorophyll a concentrations, were observed on the French Guiana continental shelf in the outer Amazon plume, with fCO2 values below 150 uatm. Here, a CO2 sink was present almost throughout the year, with a seasonal maximum of -9.2 mmol CO2 m-2d-1 observed in June 2015. However, both the CO2 and salinity distributions could vary significantly within a few days, confirming the presence of many eddies in this region. The Amazon continental shelf hence behaved as a transition zone between an inshore source of CO2 to the atmosphere and an offshore sink. Some marine phytoplankton production was detected but occurred mainly close to the French Guiana shelf. A mean net CO2 outgassing of 44 ± 43.6 mmol m-2d-1 was estimated for the area. Quantifying the CO2 flux for the entire Amazon shelf area led to a revised annual estimate of the net ocean carbon export of 2.86 1012 mol C from the region.